CERITA RAKYAT MAKASSAR TUAPPAKA SISARIKBATTANG: SUATU TINJAUAN ASPEK NILAI (Makassar’s Folklore of Tuappaka Sisakrikbattang: A Study of an Aspect of Value) - Salmah Djirong (SAWERIGADING, 2009)
Macassar’s folklore of Tuappaka Sisarikbattang is a famous story inMacassar’s sucietes. There is rich man who has four children. He asks hischildren to go and find knowledge. All of them go and promise to meet eachother in one place. At the time, after they have finished their duty to findknowledge, they meet in the agreed place. They have reached incrediblesuccesful and become some one whom king can rely on, the eldest child evenbecame king’s son in law moral values contain. In the story knowledge is animportant thing, working hard, cooperative and honest.